(untitled) (Research, Society and Development, 2022)
Kefir is a probiotic food from the Caucasus region that became popular due to its many health benefits and biotechnological potential. These properties come from proven biological activities, highlighting antimicrobial, anticancer, antidiabetic, modulation of the intestinal microbiota, as well as benefits to the gastrointestinal tract. It is prepared from the disposition of its grains, formed by a microbial consortium of yeasts and bacteria, for fermentation of a carbohydrate source. External characteristics, such as pH, temperature and oxygen concentration, directly influence the growth and characteristics of the component microorganisms. In this sense, the present work aimed to evaluate the increase in biomass of a kefir crop over 15 months. To this end, mathematical models that best described its growth along the cycles in a batch system were evaluated, the growth rates were analyzed in order to verify the correlation of seasonality of artisanal production with growth, in addition to the effect of cultivation intervals. The mathematical models indicated that, in the analyzed samples, the second order polynomial regression was the most adequate to represent the biomass accumulation along the cycles, with significant differences in the growth rates. The mathematical models indicated that, in the analyzed samples, the second order polynomial regression was the most adequate to represent the biomass accumulation along the cycles, with significant differences in the growth rates.